Pengaruh Stakeholder Engagement, Media Exposure dan Tekanan Pemegang Saham terhadap Kualitas Sustainability Report - Nurhasanah, Dinda; Afriyenti, Mayar (Jurnal Eksplorasi Akuntansi, 2024)
This research seeks to investigate the impact of stakeholder engagement, media exposure, and shareholder pressure on the quality of sustainability reports among energy sector companies listed on the Indonesia Stock Exchange. Applying a quantitative technique with a causal associative model, the study samples 19 energy companies that consistently published sustainability reports from 2017 to 2021, yielding 57 qualifying samples. Data analysis was conducted through panel data regression. The findings indicate that media exposure has a significant impact on the quality of sustainability reports, while stakeholder engagement and shareholder pressure do not show a similar influence. This study offers contributions to the field of stakeholder engagement, a topic that has been infrequently explored in Indonesia. The results suggest that companies should enhance stakeholder engagement and take media exposure into account to upgrade the quality of their sustainability reports. Further studies might broaden the sample to include other sectors and implement the latest GRI Standards.